Constructing identity : collecting Oceanic art/artefacts in New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Museum Studies at Massey University - Evans, Rose (Massey University, 2002)
This study is concerned with the collection of historic and contemporary Oceanic art forms by private collectors in New Zealand. Exploration into a recent increase in both market promotion and private collectors incorporating Oceanic art forms into their contemporary fine art collections is analysed in this research. The study sits within a body of international research into motivations behind collector behaviour and the relationship between art and artefact, yet also exists within the specific local context of New Zealand as a post colonial settler society. The objective of the study is to use qualitative methodology to interview a small sample of five case study collectors. These collectors can be positioned in an art/artefact continuum. One dealer, identified by three of the case study collectors, was interviewed to examine the complex relationship between dealer and private collectors of Oceanic art. Two aspects are explored; the recent growth of Oceanic art forms in private contemporary New Zealand fine art collections and the increasing market promotion of cultural artefacts as fine art works. The study concludes that there has been an increasing interest by collectors of contemporary New Zealand fine art to incorporate Oceanic historic and contemporary art forms into their fine art collections. The study also identified the emergence of a new type of dealer who operates in an urban context to promote both historic and contemporary Oceanic art forms within a fine art gallery environment. The dealer articulates a 'narrative of identity' symptomatic of settler primitivism since colonial settlement in New Zealand. She uses Oceanic art within the context of a fine art collection not only to facilitate the collectors' examination of individual identity but also to negotiate a sense of place within a dynamic post-colonial multicultural environment.
Keywords: Art; Material culture; Oceania; Primitive art; Collectors and collecting; New Zealand